Developing a competency model for Chinese general practitioners: a mixed-methods study - Xue Gong; Xu Zhang; Xinyan Zhang; Yixuan Li; Yang Zhang; Xiaosong Yu (BMC, 2024)
Abstract Background The Chinese government has formulated a series of policies and strengthened training of general practitioners (GPs) to support their role as "gatekeepers" of residents' health. This study aimed to explore the core competencies of Chinese GPs and develop a competency framework in line with China's actual conditions, which can provide a more scientific basis for the education, training, and evaluation of GPs. Methods Literature analysis and behaviour event interviews were conducted to build the competency dictionary and the initial version of the competency model. Two rounds of Delphi were performed to gain consensus on the final model. The questionnaire survey was carried out in 10 provinces (municipalities, autonomous regions) of China, and GPs were invited to score the importance of each competency item. The total sample was randomly divided into two groups. One group was for exploratory factor analysis (EFA), and the other was for confirmatory factor analysis (CFA) to examine the scale's reliability and validity. Results The dictionary of general practitioners' competency including 107 competency items was constructed. After two rounds of Delphi, a consensus was reached on 60 competencies in 6 domains. A total of 1917 valid questionnaires were obtained in the nationwide survey. The average importance score of all second-level indicators is 4.53 ± 0.45. The Cronbach's α coefficient is 0.984. The results of the five factors extracted by EFA showing the 68.16% cumulative explained variance variation is considered to be consistent with the six dimensions obtained by Delphi after thorough discussion. The model fitness indexes obtained by CFA were acceptable (χ2/df = 4.909, CFI = 0.869, NFI = 0.841, RMSEA = 0.065). The values of the composite reliability (CR) of the six dimensions were all greater than 0.7 (0.943, 0.927, 0.937, 0.927, 0.943, 0.950), and the average of variance extracted (AVE) were all greater than 0.5 (0.562, 0.613, 0.649, 0.563, 0.626, 0.635). The results showed that the model has good reliability and validity. Conclusion A competency model for GPs suited to China has been developed, which may offer guidance for future training and medical licensing examinations of GPs.